Overexpression of Terpenoid Biosynthesis Genes From Garden Sage (Salvia officinalis) Modulates Rhizobia Interaction and Nodulation in Soybean - Ali, Mohammed; Miao, Long; Hou, Qiuqiang; Darwish, Doaa B.; Alrdahe, Salma Saleh; Ali, Ahmed; Benedito, Vagner A.; Tadege, Million; Wang, Xiaobo; Zhao, Jian (Frontiers in Plant Science, 2021)
In legumes, many endogenous and environmental factors affect root nodule formation through several key genes, and the regulation details of the nodulation signaling pathway are yet to be fully understood. This study investigated the potential roles of terpenoids and terpene biosynthesis genes on root nodule formation in Glycine max. We characterized six terpenoid synthesis genes from Salvia officinalis by overexpressing SoTPS6, SoNEOD, SoLINS, SoSABS, SoGPS and SoCINS in soybean hairy roots and evaluating root growth and nodulation, and the expression of strigolactone (SL) biosynthesis and early nodulation genes. Interestingly, overexpression of some of the terpenoid and terpene genes increased nodule numbers, nodule and root fresh weight, and root length, while others inhibited these phenotypes. These results suggest the potential effects of terpenoids and terpene synthesis genes on soybean root growth and nodulation. This study provides novel insights into epistatic interactions between terpenoids, root development, and nodulation in soybean.